Notes about Basella alba (Basellaceae) with description of a new variety from West Bengal (India) - Das, Saubhik (Phytotaxa, 2025)
Basella alba (Basellaceae) is a species showing a high morphological variability. Currently, it is represented by two commonly cultivated forms plus one wild taxon. A morphometric analysis of some Indian populations was performed and the results obtained allow the recognition of three varieties, of which one new for science (Basella alba var. scandens var. nov.). This new infraspecific taxon differs from the others two by thin cord-like twining stem and smaller ovate-cordate leaves.